DETERMINANTS OF ADOPTION OF E-PROCUREMENT PRACTICES: A CRITIQUE OF LITERATURE REVIEW - Waithaka, Robert Kariuki; Kimani, John G. (Global Journal of Purchasing and Procurement Management, 2021)
Purpose: This study proposes sought to determine factors influencing the adoption of e-procurement practices. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. The study adopted a desktop literature review method (desk study). This involved an in-depth review of studies related to factors influencing the adoption of e-procurement practices. The search was done generally by searching the articles in the Article title, abstract, keywords. A second search involved fully available publications on the subject of e-procurement practices. The third step involved the selection of fully accessible publications. The drawing and interpretation of research findings and sense which is not a quantitative impact evaluation, was important in this context, which implies that qualitative and thematic analysis was most suitable in this study. Findings: From the study, it was noted that E-procurement has not been fully adopted by all the agencies. Further, E-security, staffing, user acceptance and top management support were the factors that were found to be influencing adoption of e-procurement. Top management support and E-security are the major influence of E-procurement adoption especially in the public sector. Unique contribution to theory, practice and policy: The study recommended that Top management support among the organizations should set goals, strategies and baselines that are necessary for the adoption of the E-procurement and follow up to ensure implementation. The study also recommended that due to the sensitivity of the data and the legal nature of orders and payments, security of data should be enhanced. Organizations should create personalized technology systems that create a demand adaptation of ICT at every level of the organizational operations